A pH-Adjustable Tissue Clearing Solution That Preserves Lipid Ultrastructures: Suitable Tissue Clearing Method for DDS Evaluation - Shintaro Fumoto; Eriko Kinoshita; Keisuke Ohta; Kei-ichiro Nakamura; Tasuku Hirayama; Hideko Nagasawa; Die Hu; Kazuya Okami; Riku Kato; Shojiro Shimokawa; Naho Ohira; Koyo Nishimura; et al. (MDPI AG, 2020)
Visualizing biological events and states to resolve biological questions is challenging. Tissue clearing permits three-dimensional multicolor imaging. Here, we describe a pH-adjustable tissue clearing solution, Seebest (SEE Biological Events and States in Tissues), which preserves lipid ultrastructures at an electron microscopy level. Adoption of polyethylenimine was required for a wide pH range adjustment of the tissue clearing solution. The combination of polyethylenimine and urea had a good tissue clearing ability for multiple tissues within several hours. Blood vessels stained with lipophilic carbocyanine dyes were deeply visible using the solution. Adjusting the pH of the solution was important to maximize the fluorescent intensity and suppress dye leakage during tissue clearing. The spatial distribution of doxorubicin and oxidative stress were observable using the solution. Moreover, spatial distribution of liposomes in the liver was visualized. Hence, the Seebest solution provides pH-adjustable, rapid, sufficient tissue clearing, while preserving lipid ultrastructures, which is suitable for drug delivery system evaluations.